Initial (and incidental) diagnosis of plasma cell neoplasm in the liver and gastrointestinal tract - Lessons to be learnt from two cases and literature review - Dorottya Laczkó; Vinodh Pillai; Dale Frank; Danielle Fortuna (Elsevier, 2022)
Extramedullary plasma cell neoplasms are an infrequently reported phenomenon in the literature to date as they can pose a diagnostic challenge due to their wide range of clinical presentation. In this review, first we present two cases of extramedullary plasma cell neoplasms involving the liver and the duodenum in which the identification of monoclonal plasma cell populations were incidental findings in the background of other disorders. With these cases and review of literature, we would like to illustrate that although plasma cells can be found under physiological conditions in many tissues, atypical distribution patterns and cytologic atypia should prompt additional workup that can identify incidental plasma cell disease at an extramedullary site.